Negotiating Islamic Legal Culture: Muslim Majority Participation under Non-Muslim Leadership in Multicultural Villages - Karim, Abdul; Nur, Dany Miftah M.; Zubair, Abi Amar (Al-Manahij: Jurnal Kajian Hukum Islam, 2025)
This study analyzes non-Muslim leadership in a Muslim-majority community through Islamic legal culture, highlighting how religious norms, legal consciousness, and local wisdom inform tolerance and coexistence. Using qualitative participatory action research, data were collected via participant observation, with in-depth interviews, and documentation, and also triangulation ensuring validity. The Jrahi community, grounded in Islamic values of ukhuwah (brotherhood), ʿadl (justice), and taʿāwun (mutual help), responded positively to a non-Muslim village head whose character and service aligned with principles of justice and public welfare in Islamic ethics. His election reflected a negotiation between Islamic normative ideals and pragmatic governance, prioritizing integrity, maturity, and leadership capacity over religious affiliation. Although peace promotion was absent from his formal vision and mission, it was realized through cooperation and preservation of local traditions consistent with the Islamic legal value of maslahah. The community’s choice sought to maintain unity, prevent conflict, and guard against both syncretism undermining ʿaqīdah and radical extremism disrupting social order. This case demonstrates how Islamic legal culture adapts within multicultural realities, offering insights into the acceptance of minority leadership in Muslim-majority settings without compromising core Islamic legal and ethical principles.